STRATEGI KOMUNIKASI DINAS KOPERASI, USAHA MIKRO, KECIL DAN MENENGAH (UMKM) KOTA PEKANBARU DALAM MEMBERDAYAKAN KELOMPOK UMKM MELALUI PROGRAM KLINIK KONSULTASI BISNIS DI KOTA PEKANBARU - Diana Putri; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Based on data from the Department of Cooperative and Micro, Small and Medium Enterprise (MSME) Pekanbaru, a growing number of MSME continues to increase each year which recorded to 13,547 units. There are a lot of MSME in Pekanbaru, however the common problems faced by MSME have not been fully solved yet. Therefore, the empowerment program for MSME owners is required to address the problems by establishing The Business Consulting Clinic (BCC). The purpose of this research is to discover the communication strategy in determining the communicator, delivering the message, defining the objectives, and media selection by Department of Cooperative and MSME in empowering the group of MSME through Business Consulting Clinic program in Pekanbaru.Firstly, this research uses descriptive qualitative methods. Meanwhile, purposive technique is choosen to determine the subject of the research. There are several sources who provide the information for this research, they are Head of Finance Department Cooperative and MSME, Head of Promotion Division, Head of Enterprise and Investment Development Division, two practioners of BCC, the beverage and herbal medicines entrepreneur as well as the embroidery and Songkok Melayu employer. Afterwards, the technique is used for data collection are interview, observation, and documentation. Data analysis technique performed by using interactive data analysis model Miles and Huberman. Lastly, to reach the validity of data in this research, the author uses the extension of participation and triangulation.Furthermore, the results showed that the communication strategy for empowering a group of MSME through BCC program is to pay attention to four factors. In one hand, strategies in determining the target are for the owners of MSME that have constraints and problems in entrepreneurship; have been active and holding a license for a Small Micro Business; and the young entrepreneurs. The communication messages are delivered in the form of an informative message with repetition and persuasive technique by giving solution in solving the problem of the owner of MSME including the knowledge and feedback in accordance with the service at the BCC program. Then, the media used are print media, electronic media and media groups. Finally, the strategy in deciding the communicators with criteria are by selecting people who work directly in doing coaching and empowerment of MSME with knowledge and experience regarding the process of empowerment of MSME would be able to understand about the BCC program.